Effect of free-choice feeding on the performance and ileal digestibility of nutrients in broilers - Cruz, V C [UNESP]; Pezzato, Antonio Celso [UNESP]; Pinheiro, D F [UNESP]; Gonçalves, J C [UNESP]; Sartori, José Roberto [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2005)
An experiment was conducted to study ileal digestibility of nutrients and to verify the ability of broilers to select feed in order to meet their requirements for protein and energy. The treatments consisted of six diets: R+S: free-choice feeding with rice bran (energy) and soybean meal (protein); C+G: free-choice feeding with corn (energy) and corn gluten meal (protein); R+G: free-choice feeding with rice bran (energy) and corn gluten meal (protein); C+S: free-choice feeding with corn (energy) and soybean meal (protein); R+C+G+S: free-choice feeding with rice bran and corn (energy) and corn gluten meal and soybean meal (protein); and BD: basal diet represented by a complete diet composed of 63% corn and 33% soybean meal. The results indicated that the adjustment to nutritional requirements does not depend only on the ability of birds to select feed. It might also depend on intake and ingredient quality, since some ingredients did not provide a balanced amount of nutrients. The birds were able to fulfill their requirements for maintenance, that is, they consumed the minimum amount of amino acids (g per day) for maximum growth. The free-choice group with corn gluten meal as the protein source had the worst performance, which indicated that this feed is not recommended as a primary source of amino acids for broilers. The C+G diet presented the highest digestibility coefficient of dry matter and crude protein, whereas the C+S diet resulted in the highest digestibility coefficient of ether extract and nitrogen-free extract, indicating that diet digestibility was affected by the type of feed used as energy and protein sources. In general, the high digestibility values indicate that broilers are able to efficiently digest and absorb the supplied feed.
Keywords: Broiler; digestibility coefficient; free-choice feeding; performance